2020
DOI: 10.1177/0883911520913905
|View full text |Cite
|
Sign up to set email alerts
|

Double coating of graphene oxide–polypyrrole on silk fibroin scaffolds for neural tissue engineering

Abstract: The desired scaffolds for neural tissue engineering need to have electrical conductivity. In this study, we doubly coated graphene oxide and polypyrrole on silk fibroin scaffolds (SF@GO-PPY) by a facile method to improve its electrical conductivity. The graphene oxide–polypyrrole double coating was distributed homogeneously on silk fibroin scaffolds. Compared with silk fibroin scaffolds, the SF@GO-PPY scaffold showed higher electrical conductivity, electrochemical property, mechanical property, and thermal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…76 When rGO was mixed with aqueous silk fibroin, rGO was evenly distributed on the silk, improving the mechanical and thermal properties. 77–79 Wu et al 80 modified GO by grafting the BMP-2 polypeptide. They then electrostatically adsorbed GO onto SF electrospun scaffolds, which further improved the biocompatibility of the SF scaffolds.…”
Section: Hybrids With 2d Nanomaterialsmentioning
confidence: 99%
“…76 When rGO was mixed with aqueous silk fibroin, rGO was evenly distributed on the silk, improving the mechanical and thermal properties. 77–79 Wu et al 80 modified GO by grafting the BMP-2 polypeptide. They then electrostatically adsorbed GO onto SF electrospun scaffolds, which further improved the biocompatibility of the SF scaffolds.…”
Section: Hybrids With 2d Nanomaterialsmentioning
confidence: 99%
“…Several examples involving combinations of synthetic and natural polymers have been reported for peripheral and nerve regeneration. For instance, Wang et al reported recently the use of silk fibroin (SF) with PPy (Wang et al, 2020). In this study, the authors showed that PPy and GO were uniformly distributed on SF scaffolds giving rise to materials with remarkable mechanical properties, electrical conductivity and superior cytocompatibility when using SH-SY5Y cells.…”
Section: Hybrid Synthetic-natural Materialsmentioning
confidence: 75%
“…The larger the area of the circular curve, the greater the electrochemical properties and the conductivity of the material are. 27…”
Section: Electrochemical Testsmentioning
confidence: 99%